Clibadiolide, a sesquiterpene lactone esterified with a homoditerpene from Clibadium pittierii - Tamayo Castillo, Giselle (1988)
The aerial parts of Clibadium pittierii afforded in addition to known melampolides two new ones, one being esterified with a homoditerpenic acid and the homoditerpenic acid itself. The structures were elucidated by high field NMR spectroscopy. The chemotaxonomy is discussed briefly.